Keeping it living : traditions of plant use and cultivation on the Northwest Coast of North America - Deur, Douglas, 1969-; Turner, Nancy J., 1947- (University of Washington Press ; UBC Press, 2005)
"Bringing together some of the world's most prominent specialists on Northwest Coast cultures, Keeping It Living is the first comprehensive overview of how Native Americans managed the landscape and cared for the plant communities on which they depended, from the Oregon coast to Southeast Alaska. It explores tobacco gardens among the Haida and Tlingit, managed camas plots among the Coast Salish of Puget Sound and the Strait of Georgia, estuarine root gardens along the central coast of British Columbia, wapato maintenance on the Columbia and Fraser Rivers, and tended berry plots up and down the entire coast." "With contributions from ethnobotanists, archaeologists, anthropologists, geographers, ecologists, and Native American scholars and elders, Keeping It Living documents practices, many unknown to European peoples, that involve manipulating plants as well as their environments in ways that enhanced culturally preferred plants and plant communities. It describes how indigenous peoples of this region used and cared for over 300 different species of plants, from the lofty red cedar to diminutive plants of backwater bogs."--Jacket